2006
DOI: 10.1111/j.1369-1600.2006.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

PRECLINICAL STUDY: Schedule‐induced alcohol drinking: non‐selective effects of acamprosate and naltrexone

Abstract: Acamprosate and naltrexone are therapeutically effective drugs that promote abstinence and prevent drinking relapse among alcohol-dependent patients, and dose-dependently decrease alcohol self-administration in animals. The purpose of this experiment was to investigate the behavioral specificity of acamprosate and naltrexone treatment in mice on alcohol drinking elicited in a schedule-induced polydipsia (SIP) task. Food-deprived male C57BL/6J (B6) mice were divided into three groups assigned to a 5% alcohol SI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 76 publications
2
30
0
Order By: Relevance
“…Moreover, it points to a specific role for the opioid system in initiating high ethanol intake as compared to the intake of a sugar reward or plain water. This is important because other animal models of high ethanol drinking, such as schedule-induced polydipsia, fail to show specificity for effects of naltrexone on ethanol drinking as compared to plain water drinking (Escher and Mittleman 2006). This result is also significant because one feature that has not yet been clearly elucidated is how motivation for ethanol is different from motivation for natural rewards (Kelley and Berridge 2002).…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, it points to a specific role for the opioid system in initiating high ethanol intake as compared to the intake of a sugar reward or plain water. This is important because other animal models of high ethanol drinking, such as schedule-induced polydipsia, fail to show specificity for effects of naltrexone on ethanol drinking as compared to plain water drinking (Escher and Mittleman 2006). This result is also significant because one feature that has not yet been clearly elucidated is how motivation for ethanol is different from motivation for natural rewards (Kelley and Berridge 2002).…”
Section: Discussionmentioning
confidence: 80%
“…In addition, doses of acamprosate of 400-450 mg/kg have been previously reported to produce reductions in general fluid consumption and body weight (Czachowski et al 2001;Escher and Mittleman 2006;Gewiss et al 1991;Heyser et al 1998;Hölter et al 1997;Le Magnen et al 1987).…”
Section: Discussionmentioning
confidence: 98%
“…Because we observed adverse effects of the high (500 mg/kg) dose of acamprosate (i.e., reductions in body weight and spontaneous locomotor activity as well as one case of mortality) and because previous reports have shown that doses of 400 and 450 mg/kg of acamprosate inhibit general behavioral output and reduce body weight in other rat strains and experimental settings (Czachowski et al 2001;Escher and Mittleman 2006;Gewiss et al 1991;Heyser et al 1998;Hölter et al 1997;Le Magnen et al 1987), we elected not to test any doses of acamprosate higher than 300 mg/kg on cocaine self-administration and reinstatement of cocaine-seeking behavior.…”
Section: Effects Of Acamprosate On Locomotor Activity and Body Weightmentioning
confidence: 94%
“…Moreover, in SIP, the substitution of water for ethanol solution-induced equivalent levels of consumption has been considered as a promising behavioral model of alcohol abuse, relating directly to the induction of compulsive alcohol drinking (Gilpin et al 2008;Mittleman et al 2003Mittleman et al , 2011Singer et al 1982;Singer and Wallace 1984;Wayner 2002). Schedule induction and ethanol polydipsia provide an opportunity to investigate the development of drinking typologies that lead to chronic, excessive voluntary alcohol consumption in animals (Colotla 1981;Falk and Tang 1988), as well as the neural substrates and pharmacology of alcohol addiction (Escher and Mittleman 2006;Mittleman et al 2011).…”
Section: The Sip Proceduresmentioning
confidence: 99%